2007
DOI: 10.1002/app.25527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of support friability and concentration of α‐olefins on gas‐phase ethylene polymerization over polymer‐supported metallocene/methylaluminoxane catalysts

Abstract: The effects of support friability (F) and ethylene/comonomer ratios were investigated over supported metallocene/methylaluminoxane catalysts prepared with nine different porous polymeric supports and various comonomer concentrations with a 2-L reactor operated in the semibatch gas-phase mode at 808C and 1.4 MPa. F of the supports was measured with a newly devised method. The performance of the supported catalysts depended on support F as follows. The average homopolymerization activities varied from less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
0
31
1
Order By: Relevance
“…This problem could arise from a high resistance of the support or from an insufficient hydraulic force of the growing polymer to breakup as soon as the nascent polymer fills the interior of the support [6,[27][28][29][30]. In fact, the activity of the majority of the metallocenes used in the present study is lower than that found in homogeneous Cp 2 ZrCl 2 and (nBuCp) 2 ZrCl 2 .…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This problem could arise from a high resistance of the support or from an insufficient hydraulic force of the growing polymer to breakup as soon as the nascent polymer fills the interior of the support [6,[27][28][29][30]. In fact, the activity of the majority of the metallocenes used in the present study is lower than that found in homogeneous Cp 2 ZrCl 2 and (nBuCp) 2 ZrCl 2 .…”
Section: Discussioncontrasting
confidence: 70%
“…Under these conditions, monomer mass transfer along the particle radius could hinder the polymerization, which subsequently reduces catalytic activity [27,29]. Experimental results addressing this issue have been reported in the literature for supported metallocene catalysts [6,27], silicasupported Ziegler-Natta catalysts [29], and Philipps catalysts [28,29]. Such studies have shown that the fragmentation is closely related to the physical resistance of the support to break into many pieces of 0.1-20 lm in diameter [27][28][29][30].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[27][28][29] The morphology of the supports and catalysts was elucidated by SEM ( Figure 7). On the other hand, both yield and texture of the catalyst affect the polymer morphology, and the catalysts are also known to replicate their morphology into the polymer particles.…”
Section: Resultsmentioning
confidence: 99%
“…The greatest of them is that diffusion limitations reduce the activity of heterogeneous catalysts in the homopolymerization of ethyelene and propylene [29].…”
Section: Gas Phase Polymerizationmentioning
confidence: 99%